Pelatihan Tari bagi Kelompok Sadar Wisata di Desa Wisata Menari Tanon Kabupaten Semarang - Paranti, Lesa; Putri, Rimasari Pramesti; Marsiana, Deva (Universitas Negeri Semarang, 2019)
Tanon is one of tourism village in Semarang Regency that has potentials in natural and human resources. The problems are 1) traditional art in Tanon needs to be developed, 2) the limit resources able to develop the art, because they studed art in autodidact. Based on the promblems, it is important to give the dance training to improve their knowledge and skill, at once create a dance to add the traditional dance as welcoming dance. The activity consists of 10 persons. The steps are making Forum Grup Discussion with the leader of Pokdarwis dan dance coordinators, training and mentoring activities, and evaluation. The method used collaborative learning. The result shows that an increase in their dancing skill, created a Lembu Tanon dance as welcoming sance. The activities carried out produce the outer covering of articles and publication in the printed and online. We hope the activities to continue autonomously by the members to dancer junior.